Strong association of phenylalanine and tryptophan metabolites with activated cytomegalovirus infection in kidney transplant recipients - Sadeghi, Mahmoud; Lahdou, Imad; Daniel, Volker; Schnitzler, Paul; Schefold, Jörg Christian; Zeier, Martin; Iancu, Mircea; Opelz, Gerhard; Terness, Peter (Human immunology, 2012)
Infection-induced inflammation triggers catabolism of proteins and amino acids. Phenylalanine and tryptophan are 2 amino acids related to infections that regulate immune responses. Polyomavirus BK (BKV) and cytomegalovirus (CMV) are important pathogens after kidney transplantation. We investigated the clinical relevance of phenylalanine, tryptophan, and tryptophan metabolites (kynurenine and quinolinic acid) plasma levels in kidney transplant recipients with active CMV (BKV−CMV+, n = 12) or BK virus infection (BKV+CMV−, n = 37). Recipients without active viral infections (CMV−BKV−, n = 28) and CMV−BKV− healthy individuals (HCs, n = 50) served as controls. In contrast to BKV infection, activated CMV infection is tightly linked to increased phenylalanine and tryptophan metabolite plasma levels (p ≤ 0.002). The association of phenylalanine (cutoff 50 μmol/L) with CMV infection demonstrates high sensitivity (100%) and specificity (94%). By contrast, kynurenine (p = 0.029) and quinolinic acid (p = 0.003) values reflect the severity of CMV infection. In this early proof-of-concept trial, evidence indicates that activated CMV infection is strongly associated with increased phenylalanine as well as kynurenine and quinolinic acid plasma levels. Moreover, tryptophan metabolite levels correlate with disease severity. Measurement of these amino acids is an inexpensive and fast method expected to complete conventional diagnostic assays.